Emerging Technologies and the Threat to South Asian Security - Dr Summar Iqbal Babar; Abu Hurrairah Abbasi (CISS Insight Journal, 2024)
The unprecedented advancements in new technologies – artificial intelligence, cyber, autonomous, and advanced conventional weaponry – are set to substantively transform the character of warfare and redefine South Asia’s security landscape. Competition for technological dominance will increase the risks of pursuing regional stability. Hence, there is a need for comprehensive cooperation, including arms control measures, such as increased transparency, to prevent accidental or unintended escalation. This paper analyses the interplay between emerging technologies and security dynamics in South Asia through deterrence theory. Due to their intangible nature, inherent imbalances, and unpredictability, emerging technologies can introduce new and less predictable aspects to deterrence. This, in turn, would pose challenges to established conventional deterrence frameworks and alter regional security calculations. India is investing significantly in advanced conventional weaponry and deterrence capabilities, which will compel Pakistan to take necessary measures to maintain balance in South Asia. India’s recent military modernization, featuring advancements in conventional weaponry, missile capabilities, and defense technologies, can reshape the regional power equilibrium. This study analyzes these transformations and offers insights for policy-makers and strategists navigating the challenges of current security paradigms in South Asia.